2021
DOI: 10.3847/1538-4357/abd850
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared and Optical Observations of Type Ic SN 2020oi and Broad-lined Type Ic SN 2020bvc: Carbon Monoxide, Dust, and High-velocity Supernova Ejecta

Abstract: We present near-IR (NIR) and optical observations of the Type Ic supernova (SN Ic) SN 2020oi in the galaxy M100 and the broad-lined SN Ic SN 2020bvc in UGC 9379, using Gemini, Las Cumbres Observatory, Southern Astrophysical Telescope, and other ground-based telescopes. The NIR spectrum of SN 2020oi at day 63 since the explosion shows strong CO emissions and a rising K-band continuum, which is the first unambiguous dust detection from an SN Ic. Non-LTE CO modeling shows that CO is still optically thick and that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 147 publications
6
49
4
Order By: Relevance
“…He I features are found to be weaker/absent in SNe Ic (e.g. SN 2007gr: Hunter et al 2009; however, in addition to this, broadline SNe Ic exhibit weak signatures of C I (SN 2020bvc: Rho et al 2021), which indicate large envelope mass stripping in such events. Additionally, SNe Ib present stronger He I λ20 580 in comparison with that displayed in the NIR spectra of SNe Ic.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…He I features are found to be weaker/absent in SNe Ic (e.g. SN 2007gr: Hunter et al 2009; however, in addition to this, broadline SNe Ic exhibit weak signatures of C I (SN 2020bvc: Rho et al 2021), which indicate large envelope mass stripping in such events. Additionally, SNe Ib present stronger He I λ20 580 in comparison with that displayed in the NIR spectra of SNe Ic.…”
Section: Introductionmentioning
confidence: 89%
“…The spectra presented are in rest-frame wavelengths and also corrected for extinction using E(B − V) = 0.063 mag (Milisavljevic et al 2013), exhibiting a decrease in flux with wavelength, typically observed in SESNe. Line identifications of NIR spectra were done following Gerardy et al (2002), Hunter et al (2009), Banerjee et al (2018), andRho et al (2021). The vertical red bands denote regions of poor atmospheric transparency.…”
Section: Nir Spectroscopic Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a broken power law for the ejecta density structure, the properties of the SN ejecta are specified by the ejecta mass (M ej ), kinetic energy (E K ), and the power-law indices of the inner and outer density distributions in the ejecta velocity coordinate (v); the inner index is set to be 0, and the outer one is denoted as n (ρ SN ∝ v −n ). We adopt M ej = 1M , E K = 10 51 ergs, and n = 10, being roughly consistent with the optical light curve modeling (Rho et al 2021). We emphasize that the details of these parameters on the ejecta properties are not important for our purpose, which is to demonstrate the need for the non-smooth CSM as argued in Section 3 in a model-independent way.…”
Section: Light Curve Models and The Csm Environmentmentioning
confidence: 68%
“…The recent development of high-cadence surveys now allows multi-wavelength follow-up observations of SNe in the infant phase (Bellm et al 2019;Graham et al 2019). SN Ic 2020oi in the nearby galaxy M100 (∼ 15 Mpc) was discovered on 7 Jan 2020, 13:00:54 (UT) in a very infant phase (∼ 1 day after the putative explosion date; 6 Jan 2020, JD 58854.0 ± 1.5) (Förster et al 2020;Horesh et al 2020;Siebert et al 2020;Rho et al 2021). In this paper, we present the data from our ALMA observations for SN 2020oi (Section 2).…”
Section: Introductionmentioning
confidence: 99%